6
$\begingroup$

For the Stirling numbers of the second kind, the following identity is well-known: \begin{align} S(n,l) = \sum_{k_1 + \cdots + k_l = n-l} 1^{k_1} 2^{k_2} \cdots l^{k_{l}}, \end{align} where the sum is taken over non-negative integers satisfying $0 \leqslant k_1 \leqslant \cdots \leqslant k_l \leqslant n- l$. Is an analogous identity known for $s(n,l)$, the Stirling numbers of the first kind?

Edit: Thanks to Raymond, the correct formula is \begin{align} s(n,l) = (-1)^{n-l} \mathop{\sum_{k_1 + \cdots +k_{n-1} = n-l}}_{0 \leqslant k_i \leqslant 1} 1^{k_1} 2^{k_2} \cdots (n-1)^{k_{n-1}}. \end{align}

$\endgroup$
5
$\begingroup$

Yes (26.8.3 of DLMF) :

$$(-1)^{n-k}s(n,k)=\sum_{1\leq b_1<\cdots<b_{n-k}\leq n-1} b_1 b_2\cdots b_{n-k} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.